Principles of Foundation Engineering - Das, Braja M. (Cengage Learning, 2024)
This edition is specifically written for undergraduate civil engineering students like you to provide an ideal balance between today's most current research and practical field applications. Dr. Das, a renowned author in the field of geotechnical engineering, emphasizes how to develop the critical judgment you need to properly apply theories and analysis to the evaluation of soils and foundation design. A new chapter discusses the uplift capacity of shallow foundations and helical anchors. This edition provides more worked-out examples and figures than any other book of its kind, along with new learning objectives and illustrative photos that help you focus on the skills most critical for success as a civil engineer. WebAssign's digital resources are also available for review and reinforcement.